A proposal for using some short films as authentic material to improve oral skill of B1 level students during the english learning process in EFL classes through video guides at the Foreign Language Department at the University of el Salvador in semester I-2016 - Barrientos Ramírez, Luis Roberto
This research study presents valuable information about a proposal for using short films as authentic material to improve oral skill of B1 level students during the English learning process in EFL classes through video guides at the Foreign Language Department at the University of El Salvador in semester I-2016. At the same time, it encompasses information about important findings of previous studies related to the importance of the use of short films activities in English as a foreign language (EFL) courses. It also presents the information about how to improve such skills. This work is divided into eight chapters: Chapter number one includes with the research design, and it features sections in which the researchers clearly demonstrate the different issues students are having regarding the oral skill which is, in this case, the description of the problem and also the objectives that the research team agreed to accomplish. Finally, the justification demonstrates why this research study is worth carrying it out and the research questions stated by the team. Chapter number two presents the theoretical framework which makes this work reliable and trustful. It provides grounded information about the usage of short films and how it can be helpful to improve oral skills. Besides, this part reveals that English students from the Foreign Language Department at the University of El Salvador, hardly ever have speaking and listening activities in their classes, it also states the importance of using authentic material during the English learning process. Chapter three includes about the Methodological Design which features the methodology and type of study; it also presents the research design used to carry out the research and the different data collection instruments and techniques that were used to obtain consistent information of the sample of study; finally, the operationalization of data. Chapter number four shows the data analysis. It is based on all the observation process to obtain information about the use of short films during an English class at Instituto Técnico Centroamericano, ITCA; the data, which was obtained by having interviewed g some teachers to later analyze all the information that was gathered and compared with the grounded theory presented by the research team. Finally, Chapter five and Chapter number six, provides valuable conclusions and recommendations of the phenomenon of study. In addition, Chapter VII presents the grounded information and reliable collected by the research team in order to accomplish this investigation. Chapter VIII includes the appendices in which readers will find the questionnaires and some other documents that were very valuable to succeed with this investigation.